التطور الدلالي عند شعراء البلاط الحمداني الشؤون المدنية والسكنية نموذجاً - حبيب ماهر; منصور عفراء (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تتناول هذه الدراسة موضوع التطور الدلالي عند شعراء البلاط الحمداني ممثلين بالمتنبي، وأبي فراس الحمداني، وكشاجم، والخالديين (أبي بكر، وأبي عثمان)، على اعتبار أن هؤلاء الشعراء لازموا البلاط الحمداني أطول فترة زمنية. تحاول هذه الدراسة الوقوف على التغييرات الدلالية التي حصلت في ألفاظ الشؤون المدنية والسكنية عند شعراء تلك الفترة، فتبدأ بالجانب النظري، وتنتقل فيما بعد إلى التطبيق والدراسة. يبدأ الجانب النظري بتعريف مفهوم التطور الدلالي، كما يدرس عوامل التطور الدلالي وأسبابه، ويعرض مظاهر هذا التطور ومجالاته، ويسلط الضوء على نتائج هذه الظاهرة اللغوية. فيما يتناول الجانب التطبيقي دراسة اللفظة بين المعجم والسياق، وما طرأ عليها من تغييرات في الدلالة، إضافة إلى دراسة صوتية وصرفية ودلالية للألفاظ لمعرفة أثر هذه البنى (الصوتية، الصرفية) في دلالة اللفظة وتغيير هذه الدلالة. This study examines the semantic development of Al- Hamdani poet laureates represented by Al-Motanabbi, Abi Firas Al- Hamdani, Kashagem, and Al- Khaledien (Abi Baker and Abi Osman). It attempts to highlight the semantic changes to the vocabulary of domicile and civil affairs used by poets of that period. So, the theoretical part begins this paper and the practical and discussion part ends it.. The theoretical part starts with a definition of the semantic development concept, dealing with its factors and causes, and shedding light on the results of this linguistic phenomenon.. The practical part handles the word with an eye on lexicon and context, and the semantic changes it has undergone, let alone discussing words semantically, morphologically, and phonologically linguistic to identify the impact these structures (morphological and phonological) have on the semantic changes to a given word.